Endothelial Progenitor Cells at the Interface of Chronic Kidney Disease: From Biology to Therapeutic Advancement - Coppolino, Giuseppe; Cernaro, Valeria; Placida, Giordano; Leonardi, Giuseppe; Basile, Giorgio; Bolignano, Davide (Current Medicinal Chemistry, 2018)
Background: The ‘epidemic’ diffusion of chronic kidney disease (CKD) needs the development of new therapeutic approaches to slow down the progression to end-stage renal disease. Endothelial Progenitor Cells (EPCs) are promising tools for the treatment of many human diseases as they promote the repair of damaged tissues. They were also suggested as therapy to repair renal tissue after an injury. Strategies using EPCs to induce a reparative process with functional restoring of a diseased kidney or to delay CKD are of two types: direct stem cells infusion or stimulating endogenous release of EPCs. The repair process following endothelial damage occurs in three steps: 1) mobilization from bone marrow; 2) homing on the sites of vascular injury; 3) incorporation of the endothelium into the injured blood vessels. Objective: In this narrative review we pointed our view to the role of EPCs in endothelial repair and the potential in retarding the progression to renal function loss. Conclusions: Physicians need the development of new preventive strategies for detecting patients at risk and discover renal damage. In this way they could slow, by a conservative therapy, the evolution of renal disease and decrease associated morbidity. EPCs have instead well recognized reparative capabilities in many organs. We summarized some recent preclinical and clinical models of EPCs mobilization during CKD and we emphasized the potential use of EPCs to slow the progression of renal disease.
Keywords: CKD